MathCityMap: Motivating students to engage in mathematics through a mobile app-supported math trail program - Cahyono, Adi Nur; Ludwig, Matthias (Gesellschaft für Didaktik der Mathematik, 2017)
Mathematics has functions in daily life – both individual and social – and occupational life. However, public understanding of mathematics is unsatisfactory and only a few are involved in mathematics during their schooldays with pleasure (Behrends, 2009, p. 1). At school, and globally, mathematics is sometimes perceived as a difficult and abstract subject. Internationally, by the eighth grade, only about one-fourth enjoys learning mathematics (Mullis et al., 2011, p. 325). It leads mathematicians and mathematics educators to think of popularizing mathematics to the public. A variety of projects in numerous countries took place to raise public awareness of mathematics. The MATIS I Team from Goethe University Frankfurt has also given attention to this subject by developing the MathCityMap-Project, a project of mobile app-supported math trail program. Since 2013, this project began to be implemented in Indonesia, tailored to the country’s situation. In the first study, the math trails have been designed in several locations and a mobile app was also created (Cahyono, Ludwig, & Marée, 2015). Subsequently, in the second study, students have carried out the mobile app-supported math trail program and we explored its potential to motivate students to engage in mathematics. Further, we report the results of this study through this paper.
Beiträge zum Mathematikunterricht; 51, 2017
Keywords: 510